Meningkatkan Motivasi Belajar Pendidikan Agama Islam (PAI) Siswa Kelas V SDN Leran Kecamatan Manyar Gresik Melalui Model Pembelajaran Kooperatif Tipe Tiga (Teams Games Tournaments) - L, Khomsah (PGSD Universitas WR Supratman Surabaya, 2016)
To facilitate authors in the conduct of research on the field and in the processing of the result of the study, the one based on the description of the background of the above, the author consider it important to make formulation of the problem and determine the research object, among others namely the problem: 1) How is the motivation to learn Class V student of SDN Leran Manyar District of Gresik in the subject of Islamic education? 2) To what extent the cooperative learninf model TGT (Teams games tournament) can affect learning motivation of Islamic Religious Education (PAI) Class V student of SDN Leran Manyar District of Gresik. This research was conducted in Class V semester 1 at SDN Leran Manyar District of Gresik, with a number of class V as many as 30 students, the condition of specificity allows the students ability levels and absorption of these students vary greatly. Researcher are Islamic Education teacher at SDN Leran Manyar District of Gresik. In accordance with the formulation of the problem and the purpose of research it can generally be concluded that the result for student at SDN Leran District of Manyar Gresik, can improve through learning using Cooperative Learning model TGT (Teams games tournament).